Inter-individual and inter-regional variability of breast milk antibody reactivity to bacterial lipopolysaccharides - Crone, Lisa; Sobek, Jens; Müller, Nicole; Restin, Tanja; Bassler, Dirk; Paganini, Daniela; Zimmermann, Michael B.; Zarnovican, Patricia; Routier, Françoise H.; Romero-Uruñuela, Tais; Izquierdo, Luis; Hennet, Thierry (Frontiers in Immunology, 2024)
Breast milk is a vital source of nutrients, prebiotics, probiotics, and protective factors, including antibodies, immune cells and antimicrobial proteins. Using bacterial lipopolysaccharide arrays, we investigated the reactivity and specificity of breast milk antibodies towards microbial antigens, comparing samples from rural Kenya and urban Switzerland. Results showed considerable variability in antibody reactivity both within and between these locations. Kenyan breast milk demonstrated broad reactivity to bacterial lipopolysaccharides, likely due to increased microbial exposure. Antibodies primarily recognized the O-antigens of lipopolysaccharides and showed strong binding to specific carbohydrate motifs. Notably, antibodies against specific Escherichia coli O-antigens showed cross-reactivity with parasitic pathogens like Leishmania major and Plasmodium falciparum, thus showing that antibodies reacting against lipopolysaccharide O-antigens can recognize a wide range of antigens beyond bacteria. The observed diversity in antigen recognition highlights the significance of breast milk in safeguarding infants from infections, particularly those prevalent in specific geographic regions. The findings also offer insights for potential immunobiotic strategies to augment natural antibody-mediated defense against diverse pathogens.